Neither 'Friendship Farm' nOR 'Land Grab:' Chinese Agricultural Engagement in Angola - Zhou Jinyan (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2015)
Chinese-Angolan agricultural cooperation can be divided into two phases, beginning in 2004. In the first period, from 2004 to 2008, Chinese engagement focused on infrastructure construction. Since 2008, cooperation has centered on the development of comprehensive farm projects supported by credit from the China Development Bank. These projects are not intended to solve China's food security problem, but are instead aimed at improving Angola's agricultural capacity and food production. This paper finds that the "Angola Mode" of cooperation challenges the common perception of an oil-centric relationship. However, Angola's needs and Chinese finance are not currently well-aligned, and the long-term sustainability of Chinese engagement is questionable.
Keywords: 330